Pelaksanaan Surat Kuasa Membebankan Hak Tanggungan di Koperasi Simpan Pinjam Swastika Mataram - Putu Ayu Cattelya Asri Yanthi (Jatiswara, 2016)
The purposes of this study were to analyze the implementation of the power of attorney imposing mortgage right, to analyze the factors that affect the implementation of the power of attorney imposing mortgage right at Swastika Credit Unions Mataram, and to analyze the dispute resolution process of the power of attorney imposing mortgage right if it was not registered as a deed of mortgage right at Swastika Credit Unions Mataram. The method used was normative-empirical law research, using law approach, concept approach, and sociological approach. The data analysis used was qualitative in order to gain clarity and truth so as a clear picture of the issues examined is obtained. These results indicated that the implementation of the power of attorney imposing mortgage right at Swastika Credit Union Mataram began by submitting an application by the debtor. The factors that obstructed the implementation of the power of attorney imposing mortgage right at Swastika Credit Union Mataram were (1) the inhibiting factor of both creditor and the debtor, and (2) the inhibiting factor of the National Land Agency Office. The dispute resolution process of the power of attorney imposing mortgage right performed by Swastika Credit Union Mataram was toward the mechanism of giving a warning letter to the debtor.